Uniaxial behavior and constitutive model of reinforcement confined coarse aggregate UHPC. (15th March 2020) - Zeng, Xianzhi; Deng, Kailai; Liang, Huanwei; Xu, Rongyao; Zhao, Canhui; Cui, Bing
Highlights: This study investigated the axial behavior of coarse aggregate ultra-high-performance concrete (CA-UHPC). On the basis of physical test results, the theoretical derivation of uniaxial constitutive model of the confined CA-UHPC was conducted. Abstract: The authors investigated the uniaxial behavior of reinforcement-confined coarse aggregate ultra-high-performance concrete (CA-UHPC) under compressive deformation. Twelve large-scale reinforcement-confined CA-UHPC column specimens were loaded, subjected to the uniaxial compressive deformation. The investigated variables included the volumetric stirrup ratio, sectional reinforcement ratio, and volumetric steel fiber ratio of the CA-UHPC. All specimens exhibited quasi-brittle failure modes and similar stress-strain relationships. The peak compressive stress and its corresponding reinforcement strain that confined the CA-UHPC had significant discrepancies relative to predictions made by classic confined concrete models. Theoretical derivation of uniaxial constitutive model of the confined CA-UHPC was conducted based on the test results. The internal confining effect was developed by considering the tensile capacity of the CA-UHPC. The theoretical solution indicated that the internal confining effect was dominant in comparison with the external confining effect of the stirrup. The tensile property of the CA-UHPC was the key factor influencing the overall uniaxial behavior of reinforcement-confined CA-UHPC. The authors propose a constitutive model of confined CA-UHPC. Three supplementary specimens were tested to verify the accuracy and applicability of this constitutive model, and the obtained test results demonstrated the model's effectiveness.